The Effect of Hollow Sphered Structure on Stress Shielding Reduction - Mohammadreza Yazdifar; Ibrahim Esat; Mahshid Yazdifar (European Scientific Journal, ESJ, 2018)
Bone mechanics and traditional implant materials cause a frequent problem for patients of total hip arthroplasty (THA): the bone becomes shielded from the loading. This will result in loosening of the implant, pain, and therefore revision surgery will take place to correct the issue. The current study, a methodology is developed for creating an innovative structural design that extracts volume in the shape of spheres from the samples, in order to focus solely on expected behaviour within the samples and bone. The design decreases extreme stresses carried by samples and pass them onto the remaining bone. Finite element analysis was applied to various models with different complex internal structures that contain hollow spheres close to surface. Moreover, compression test was applied to solid sample and the experimental case containing hollow spheres. This approach was to investigate the effects of spherical hollow structure near the side surface and its bonesample interface. The models containing hollow spheres have smaller young modulus and strength in comparison to the solid sample. The hollow spherical structures reduce the stress shielding and they transfer more stress onto the bone compared to the solid model. This approach also re-structures a hard material such as stainless steel to enhance osseointegration. The reduction of the young modulus and stress directly depends on the volume of the spheres in the models. However, there is a range defined for the volume that could be extracted from solid structure to achieve the most effective outcome.